Interview with Micha Espinosa and Garrett Johnson - Ybarra, Patricia (Performance Matters, 2020)
In this interview with Fitzmaurice Voicework practitioner and La Pocha Nostra performer Micha Espinosa and her collaborator Garrett Johnson, Patricia Ybarra and her interlocutors ask: "How do we fight through sound against the state under fascism and racial capitalism?"